2003
DOI: 10.1061/(asce)0899-1561(2003)15:4(400)
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Field Manufactured Cast-Concrete Products Utilizing Recycled Materials

Abstract: This investigation was performed to develop technology for manufacturing cast-concrete products using Class F fly ash, coal-combustion bottom ash, and used foundry sand. A total of 18 mixture proportions with and without the by-products was developed for manufacture of bricks, blocks, and paving stones. Replacement rates, by mass, for sand with either bottom ash or used foundry sand were 25 and 35%. Replacement rates, by mass, for portland cement with fly ash were 25 and 35% for bricks and blocks, and 15 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 2 publications
(1 reference statement)
4
25
0
1
Order By: Relevance
“…The increase in drying shrinkage due to partial or full replacement with SFS has also been noted by other researchers [6,7]. Khatib and Ellis [6] replaced standard sand with SFS by 25, 50, 75 and 100%, and observed that drying shrinkage increased along with SFS content.…”
Section: Drying Shrinkagementioning
confidence: 62%
See 3 more Smart Citations
“…The increase in drying shrinkage due to partial or full replacement with SFS has also been noted by other researchers [6,7]. Khatib and Ellis [6] replaced standard sand with SFS by 25, 50, 75 and 100%, and observed that drying shrinkage increased along with SFS content.…”
Section: Drying Shrinkagementioning
confidence: 62%
“…Loss of strength due to SFS replacement has also been noted by other researchers [6,7] although Siddique et al [1,5] reported improvement in compressive strength with an increase in SFS amounts up to 30%. Kraus et al [10] reported the possibility of a reaction between relic organic materials in SFS (from processing of metals) and chemical admixtures such as HRWRs and viscosity-modifying admixtures, that may cause an increase in air content, and result in strength loss.…”
Section: Compressive Strengthmentioning
confidence: 64%
See 2 more Smart Citations
“…The compressive strength decrease in cementitious materials is due to the presence of binder in foundry sand, as pointed out in [20,29,30]. The binder, composed by a very fine powder of carbon and clay, causes a loose of contacts and links between the cement paste and the aggregate.…”
Section: Resultsmentioning
confidence: 99%